Determinants Of Corporate Income Tax Revenue In Latin America - Listikarini, Dian Irsalina; Wijaya, Suparna (Educoretax, 2024)
Taxes are considered as an important fiscal policy tool in catalyzing inclusive economic growth and achieving the Sustainable Development Goals. Latin America as a region with great natural resource potential, still has a narrow tax base due to problems of law enforcement, tax incentives and tariff reductions. The corporate income tax that significantly increases revenue in the Latin America/LAC region in 2019 around 3.7 percent of GDP is interesting to study. Therefore, this research was conducted to examine the determinants of corporate income tax revenue in the Latin American. This study uses panel data on 12 countries in Latin America in the 2008-2018 period. The statistical method used is a quantitative method with multiple linear regression. Based on testing the panel-corrected standard error estimation model is the best model. The results show that all independent variables simultaneously affect tax revenue. The variables of economic growth, FDI inflows, land area, and trade openness partially have a significant positive effect on corporate income tax revenues. Meanwhile, the tax attractiveness index variable has a significant negative effect on corporate income tax revenue in the Latin American. In addition, from the moderating variable, trade openness only managed to moderate the relationship between FDI inflows and corporate income tax revenues with a weakening result, and failed to moderate the relationship between economic growth and corporate income tax revenues. Based on the results of this study, it is necessary to further review the international trade policies in the Latin American because trade openness still tends to have no effect and even weaken the positive relationship between FDI inflows and corporate income tax revenues.